Sustainable financing ecosystem for cocoa irrigation in Ghana: a literature review - Sarpong, D. B.; Mabhaudhi, Tafadzwanashe; Minh, Thai Thi; Cofie, Olufunke O. (CGIAR Initiative on West and Central African Food Systems Transformation, 2022)
Based on a systematic literature review using scientific database search engines and an opportunistic review of published and unpublished government, international and nongovernmental organization reports on cocoa from the internet, the paper explores sustainable irrigation financing feasibility and the potential for different cocoa systems. We design a conceptual framework and propose a sustainable financing ecosystem for supplemental irrigated cocoa farming in Ghana and a qualitative data collection tool based on the conceptual framework and insights from the literature review.